DAUN KELOR (Moringa oleifera) SEBAGAI ANTIBAKTERI TERHADAP INFEKSI BAKTERI Escherichia coli - Rida Emelia; Dhanty Dwiyanti Safitri; Hilmi Andriyani (INFOKES (Informasi Kesehatan), 2020)
The antibacterial activity of ethanol extract 96% of Moringa leaf (Moringa oleifera L) was carried out on againts Escherichia coli bacteria. This study aims to determine the antibacterial activity of Moringa Oleifera L extract against test bacteria. Antibacterial activity of the extract was tested by agar diffusion method. Furthermore extract solution with a concentration of ethanol moringa leaf extract (Moringa Oleifera L) at a concentration of 6%, 8%, 10%. From the test of antibacterial activity, it is known that the ethanol extract 96% of Moringa leaf (Moringa Oleifera L) can kill the test bacteria with a concentration of 10% has an average inhibition of 18.83 mm which is included in the strong category. Concentration of 8% has an average inhibition of 10.33mm which is included in the strong category and for a concentration of 6% has an average inhibition zone of 7.83mm which is included in the medium category.